KADIN DIŞ GENİTAL ORGANINA UYGULANAN KISITLAYICI TAHRİPKAR SÜNNET ŞEKİLLERİ (BİR ÜREME SAĞLIĞI SORUNU): OLGU SUNUMU - AKSU, M. Feridun; ORAL, Engin (Cerrahpaşa Medical Journal, 2014)
Background. Female genital mutilation is based on sociocultural and traditional patterns dating back to more than two thousand years in mainly subsaharan Africa, the MiddleEast, Arab peninsula, and some Southeast Asian communities. According to the World Health Organization, approximately 120 million African women are mutilated. Observation. We present a Subsaharan African girl who had undergone infubilation during her childhood and had applied for the deinfibulation procedure.